Determination of Exemplary Lecturer Decision Making with Modified Attributes and Criteria Prioritization Technique - Usanto; Lela Nurlaela; Reza Syahrial (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
The problem of determining exemplary lecturers is included in the multi-criteria decision making problem because the assessment can be based on predetermined assessment criteria. Consequently, determining exemplary lecturers is an important aspect of improving the quality of education in an institution. In order for the final outcomes of exemplary lecturers to be objective and to examine various values for each criterion and criterion characteristic, decision-making processes are obviously required. Consequently, the goal of this study is to provide a model for evaluating the performance of exemplary lecturers by employing decision making with changed criterion characteristics and criteria prioritization strategies based on the Rank Order Centroid (ROC) method. At the end of the procedure, the best alternative will be chosen based on the choice assessment model for identifying excellent lecturers with a case study at institution XYZ. Analysis of the final results revealed that the decision assessment model was influenced by modifying the assessment attributes using a Likert scale. The final results revealed that one of three alternative candidates for exemplary lecturer was selected based on alternative values for each criterion.